Bloodstain pattern analysis: examining the effect of wind blow on passive bloodstain pattern dropped from different heights - Sheng, Chia (Universiti Sains Malaysia, 2025)
Bloodstain pattern analysis serves vitally in crime scene investigation by reconstructing the bloodshed events and providing information on the assailant, victim and crime nature. Passive bloodstain pattern enables the estimations of blood source’s height which could potentially correlate with the height of assailant or victim. However, a bloodletting crime occurring at outdoor environment introduces uncontrollable and unpredictable external factors such as wind blow which can interfere with the usual behaviour of blood leaving the body, hindering the correct interpretation of bloodstain evidence. Additionally, limited research has been done on the effect of wind blow on passive bloodstain pattern, especially when incorporating with different heights of blood source. This study aims to examine the effects of wind velocity and height of blood drop fall on the position shift and physical characteristics of passive blood drop stain, as well as how prolonged exposure to wind blow affect the stain’s physical appearance. In this study, a single drop of blood was gently dispensed from the pipette tip using a micropipette onto a smooth white floor tile under each combination of wind velocity category and fall height. The data obtained were statistically analysed using multiple linear regression. The findings showed that wind velocity and its combined effect with fall height caused increase in the horizontal (x) position shift for up to 15.70 cm but had no significant effect on the vertical (y) position shift. The shrinkage observed on majority of the bloodstains obliterated their original physical characteristics, hence no relationship was found between wind velocity and height of fall with width, length, width-to-length ratio, number of spines, number of satellite stains, angle of impact, and glancing angle. The bloodstain’s shape was found to be not distorted from sphericity much and no directionality was revealed on the stain when blood drop fell passively from 60 cm height across different categories of wind velocity. To conclude, this study demonstrates the unpredictable and distortable passive blood drop stain at outdoor environment and suggests careful consideration of wind blow and height of blood drop fall effects by the investigators when dealing with bloodstain evidence, especially at actual outdoor crime scenes